APPLICATION OF LEAN CONCEPT TO SHIP SAFETY INSPECTION: A CASE STUDY AT PORT OF SURABAYA - F. Cahyadi (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2012)
The Lean Concept is a mindset widely used in various industries seeking for efficiency and effectiveness through improvement of process flow and elimination of waste. This research applies lean thinking to ship safety inspection at Port of Surabaya to investigate the existing procedure and to identify the wastes and non-value-add (NVA) activity. It used a combination of literature review, examination on the data of 520 inspections that have been carried out to 201 ships in the last two years (2009 - 2011), investigation on related regulations and guidelines, observation on the actual conduct of inspection, and interview with 59 marine inspectors and ship officers. Analysis is conducted using Value Stream Mapping (VSM). It is found that the existing procedure lacks significant impact in terms of imposing a reduction in the total number of detected deficiency between the earlier and subsequent inspections. Only 37% of the ships experience a reduction, indicating that the performance of inspection is currently at the level of 37 on a 100-point scale. It was mainly due to severe violation of the regulations, which is demonstrated by the issuance of ship certificate regardless of corrective action undertaken relating to the detected deficiency. Keywords: Lean concept, ship safety inspection, value stream mapping.